Role of Oxidative Stress in Mitochondrial Function: Relevance for Liver Function - Jie Xu; Zhihui Feng (MDPI AG, 2023)
The traditional recognition of mitochondria as powerhouses that generate ATP and reactive oxygen species (ROS) via oxidative phosphorylation and the tricarboxylic acid cycle has ceased [...]